Paws off the pearl! - Stilton, Geronimo (Stilton, Geronimo. Cavemice, 2016)
When the Cavemice discover a giant oyster in the lagoon near Old Mouse City, they call on Geronimo Stiltonoot to help them fish it out of the water before the saber-toothed tigers find the pearl.